Service platform architecture reconstruction based on microservices - Dongliang GUAN (Dianxin kexue)
Business platform reconfiguration is one of the important measures to undertake China Telecom’s CTNet 2025 plan,implement network reconfiguration and promote network intelligence.The problems existing in the business platform were analyzed,and the evolution goal of taking micro-service as the core concept were put forward,standardizing the general framework and open standards of the platform,and reconstructing the software framework of the business platform.And through the establishment and improvement of basic platforms,standardization and promotion of micro-service transformation of business/application platforms,resource planning and environmental deployment plans,the specific restructuring work was promoted.The resource utilization rate,development efficiency,automatic resource scheduling,deployment efficiency and other aspects of the platforms before and after the reconfiguration were compared and analyzed,and the initial results of the implementation of the business platform reconfiguration were given.Reference for the planning,development and deployment of similar platforms in the industry was provided.